Large-scale invasion of western Atlantic mesophotic reefs by lionfish potentially undermines culling-based management - Andradi-Brown, D; Vermeij, M; Slattery, M; Lesser, M; Bejarano, I; Appeldoorn, R; Goodbody-Gringley, G; Chequer, A; Pitt, J; Eddy, C; Smith, S; Brokovich, E; et al. (Springer International Publishing, 2016)
The detrimental effects of invasive lionfishes (Pterois volitans and Pterois miles) on western Atlantic shallow reefs are well documented, including declines in coral cover and native fish populations, with disproportionate predation on critically endangered reef fish in some locations. Yet despite individuals reaching depths >100 m, the role of mesophotic coral ecosystems (MCEs; reefs 30-150 m) in lionfish ecology has not been addressed. With lionfish control programs in most invaded locations limited to 30 m by diving restrictions, understanding the role of MCEs in lionfish distributions remains a critical knowledge gap potentially hindering conservation management. Here we synthesise unpublished and previously published studies of lionfish abundance and body length at paired shallow reef (0-30 m) and MCE sites in 63 locations in seven western Atlantic countries and eight sites in three Indo-Pacific countries where lionfish are native. Lionfish were found at similar abundances across the depth gradient from shallow to adjacent MCEs, with no difference between invaded and native sites. Of the five invaded countries where length data were available three had larger lionfish on mesophotic than shallow reefs, one showed no significant difference, while the fifth represented a recently invaded site. This suggests at least some mesophotic populations may represent extensions of natural ontogenetic migrations. Interestingly, despite their shallow focus, in many cases culling programs did not appear to alter abundance between depths. In general, we identify widespread invasive lionfish populations on MCE that could be responsible for maintaining high densities of lionfish recruits despite local shallow-biased control programs. This study highlights the need for management plans to incorporate lionfish populations below the depth limit of recreational diving in order to address all aspects of the local population and maximise the effectiveness of control efforts.